Idiopathic Unilateral Adrenal Haemorrhage and Adrenal Mass: A Case Report and Review of the Literature. (10th April 2013) - Christoforides, Christos; Petrou, Athanasios; Loizou, Marios
Abstract : We report an unusual case of idiopathic unilateral adrenal haemorrhage (AH) in a 55-year-old patient. This rare case had two characteristics that made it worth of report. First, idiopathic adrenal haemorrhage is very uncommon, and second it was presented as a huge, 23 cm diameter and 2, 123 gr weight, "silent" adrenal mass. It is important to distinguish a benign lesion like this from a neoplasm, although we were not able to identify it preoperatively and the diagnosis was only made after the excised specimen was examined by a group of experienced histopathologists. Only a few similar published cases, to our knowledge, are described in the worldwide literature and even fewer of this size.